Key Features of Indonesia’s State Capitalism Under Jokowi - Kyunghoon Kim (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
State capitalism has been expanding rapidly since President Joko Widodo came into power in 2014. During the past decade, the absolute size of state-owned entities has grown notably, and many have acted as ‘agents of development’ in charge of conducting government-led projects, especially in the area of physical infrastructure. While this trend and characteristics are reminiscent of the previous surge of state capitalism under Suharto before the 1997 Asian financial crisis, there also exist significant differences. First, state capitalism is surging in an economy that has been liberalised to a significant degree compared to the past. Furthermore, state capitalism is expanding along with the government’s efforts to improve the business environment for the private sector through market liberalisation. In the case of state-led infrastructure development, it is legitimised by emphasising the importance of improving connectivity in vitalising the private sector. Second, state capitalism is surging in the context of political democracy, as opposed to authoritarianism. Therefore, the mobilisation and management of state-owned entities and the side effects of those efforts are closely scrutinised by various stakeholders. The government needs to respond to their criticisms if it wishes to continue using state capitalism as an important engine for economic development.